Odd Couples Friendships at the Intersection of Gender and Sexual Orientation - Muraco, Anna (Duke University Press, 2012)
Odd Couples examines friendships between gay men and straight women, and also between lesbians and straight men, and shows how these "intersectional" friendships serve as a barometer for shifting social norms, particularly regarding gender and sexual orientation. Based on author Anna Muraco's interviews, the work challenges two widespread assumptions: that men and women are fundamentally different and that men and women can only forge significant bonds within romantic relationships. Intersectional friendships challenge a variety of social norms, Muraco says, including the limited roles that men and women are expected to play in one another's lives. Each chapter uses these boundary-crossing relationships to highlight how key social constructs such as family, politics, gender, and sexuality shape everyday interactions. Friendship itself-whether intersectional or not-becomes the center of the analysis, taking its place as an important influence on the social behavior of adults.